Hepatitis B among immigrants from Myanmar: Genotypes and their clinical relevance. Issue 2 (26th September 2017) - Schulz, Thomas R.; Edwards, Rosalind; Thurnheer, M Christine; Yuen, Lilly; Littlejohn, Margaret; Revill, Peter; Chu, Melissa; Tanyeri, Firuz; Wade, Amanda; Biggs, Beverley‐Ann; Sasadeusz, Joseph
Abstract : Hepatitis B virus (HBV) from 76 adult immigrants in Australia from Myanmar was characterized to determine the prevalence of different HBV genotypes and subgenotypes. A mutational analysis was then performed to determine the presence of clinically significant mutations and correlate them to clinical outcomes. Initial genotyping revealed 68 patients with genotype C (89.5%) and eight patients with genotype B (10.5%). Phylogenetic analysis revealed the large majority of the genotype C infections were of subgenotype C1 (67/68). Sequencing of the HBV polymerase gene (and overlapping surface gene) revealed no mutations associated with antiviral resistance. HBV surface gene mutations were detected in 10 patients with subgenotype C1. HBV BCP/PC sequencing was obtained for 71/76 (93%) patients. BCP and/or PC mutations were identified in 57/71 (80%) of PCR positive patients. Treatment had been commenced for 15/76 (18%) patients, a further 26 untreated patients were in a stage of disease where HBV treatment would be considered standard of care. It was identified that genotype C1 is the predominant sub‐genotype in this population. Genotype C is known to be associated with increased risk of development of HCC. This highlights the need for screening for HCC given the potential for the development of liver cancer. It was also identified that people with HBV were potentially not receiving optimal therapy in a timely fashion.